Acute lymphoblastic leukemia in Indian children at a tertiary care center: A multiparametric study with prognostic implications - Shweta Jha; Dinesh Kumar (Wolters Kluwer Medknow Publications, 2021)
Background: Leukemia is a varied group of hematological malignancies due to uncontrolled proliferation of blast cells. Among childhood leukemias, acute lymphoblastic leukemia (ALL) comprise 70%-80% of all childhood leukemias in India. The current study aims to report the various prognostic markers of disease severity. Methodology: Bone marrow and peripheral blood samples from 20 patients of ALL were subjected to cytogenetic and flow cytometric analysis after recording clinical history and laboratory findings. Patients were classified according to immunophenotyping markers.: For risk stratification, patients were divided into two subgroups B ALL and T ALL. The age group of majority of patients was 1-9 years (90%) with 5% each belonging to <1 and >9 years. Male: female ratio was 1.1:1. Results: Hepatosplenomegaly, lymphadenopathy, and mediastinal involvement was found in 45%, 40%, and 5% of patients, respectively. Hemoglobin levels <5 g/dl and >5 g/dl were seen in 50% of patients in each range. White blood cell counts >50,000 were seen in 3 (15%) of patients. Cytogenetic analysis revealed hypodiploid karyotype for majority (64%) of cases, normal karyotype in 28% and hyperdiploidy in rest (7%). Structural aberrations like t (21;4), del (5p), dic (5) were found all in B ALL subgroup. Patients were stratified into high and standard risk groups based on good and prognostic factors. Conclusions: This study reinforces the significance of immunophenotyping cytogenetics, clinical presentation as a prognostic tool, and their significance in risk stratification.